Raman and Sers Study of N-Acetyl-5-Methoxytryptamine, Melatonin-The Influence of the Different Molecular Fragments on the Sers Effect - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
In this work a detailed experimental Raman and SERS study on melatonin is reported. Additional density functional theory (DFT) with the hybrid exchange-correlation functional B3LYP, in combination with the 6-311++G(d,p) basis set have been performed. Scaled quantum mechanical force field (SQM FF) method for the prediction of the vibrational spectra is used to determine the geometrical, energetic and vibrational characteristics of the molecule. The DFT-computed structural parameters and harmonic vibrational wavenumbers reproduce the experimental data very well and help to characterize the vibrational behaviour of the adsorbed species. The assignment of the normal modes obtained by calculations was supported by previous vibrational studies on the distinct functional groups present in melatonin. The SERS study was carried out with particular emphasis on the interaction and adsorption of the different parts of the molecule to the gold colloidal surface. Furthermore, the adsorption behavior of melatonin on colloidal Au surface is deduced from the SERS selection rules and analysis of the calculated molecular electrostatic potential (MEP). (C) 2015 Elsevier B.V. All rights reserved.